Innovation of Form and Function of Banyumulek Pottery Craftsmanship in Lombok as Heritage of Traditional Culture - Muka, I Ketut; Suardana, I Wayan (Harmonia: Journal of Arts Research and Education, 2024)
The pottery craftsmanship of Banyumulek, a cultural heritage of the Lombok community, has undergone a transformation over time. The embodiment of cultural concepts, ideas, and forms has transitioned from functional to aesthetic values, particularly due to the influence of tourism development in Lombok. This research employs a qualitative descriptive method to explore innovations in the form and function of Banyumulek pottery. Data was collected through observation, interviews, and documentation, focusing on various forms and types of pottery in Lombok. Key informants included business owners and pottery craftsmen in the Kediri District, West Lombok. Findings indicate a change in the pottery-making process from traditional to semi-modern. The forms of pottery have evolved from simple to more decorative, and their function has shifted from practical to aesthetic. This innovation is part of a continuous cultural heritage and plays a crucial role in Lombok’s tourism industry. Changes and innovations in Banyumulek pottery reflect economic and tourism growth and affirm the values of the social and cultural identity of the local community. This research highlights the importance of preserving cultural heritage and the adaptive nature of the craft industry in the face of changing times.